Convivencia escolar policies in Latin America: Four perspectives for comprehension and action - Morales, Macarena; López, Verónica (Education Policy Analysis Archives, 2019)
Many Latin American countries have enacted policies related to convivencia escolar, where we can see different emphasis in its conceptualization. It is important to study the diversity of understandings and purposes of the policies, because there are different strategies and interventions that arise from them. In this study we analized the approaches of convivencia escolar, conducting a qualitative documentary analysis of educational policies of 18 countries of the region. The results describe four perspectives of comprehension and action for convivencia escolar: democratic, public security, infant-juvenile mental health, and managerial. Implications of each perspective for the management of convivencia escolar and for educational challenges of the region are discussed.